A Cooperative City. A dream Come True - Yu. P. Voronov (Мир новой экономики)
The article explores the process of creating a large cooperative housing complex in a district of New York. It highlights the unique circumstances that made the cooperative City project possible in the United States. The article also examines the efforts of European countries to foster urban residents’ involvement in urban development. It provides examples of innovative solutions implemented by the population of various European cities. The article delves into the Russian experience of utilizing public initiatives to enhance urban development and improve the quality of life. It emphasizes that the promotion of cooperation in urban life is supported by both governmental authorities and individual citizens and local communities. The article highlights a new phase in this process — changes in urban planning, with the transition from general to master plans becoming part of federal policy.